2007
DOI: 10.2174/092986707780059689
|View full text |Cite
|
Sign up to set email alerts
|

Building a Bridge Between Clinical and Basic Research: The Phenotypic Elements of Familial Predisposition to Type 1 Diabetes

Abstract: Familial aggregation has been shown for type 1 diabetes (T1D) although the nature of the factors (environment and/or genetics) responsible remains unclear. Familial clustering of diabetic nephropathy as well as of increased cardiovascular morbidity and early mortality has also been observed. This review describes the nearly 20 years history of our investigation in parallel with contemporary literature. The story is presented from the early years' strong focus on possible markers of T1D nephropathy (urinary alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Data from Reis et al [52] showed that in comparison with healthy individuals, patients with T1DM exhibited an increase in ROS generation, while plasma antioxidant status remained unaltered. Matteucci et al [53] demonstrated a disturbed antioxidant status in first-degree relatives of patients with T1DM, which may have been caused by a general pro-oxidative background resulting from an impaired erythrocyte redox system. In the present study, TaS in the siblings of patients with T1DM was significantly lower than in the controls, and the amount was comparable to that of patients with diabetes.…”
Section: Intra-erythrocyte Antioxidant Enzymes and Tasmentioning
confidence: 99%
“…Data from Reis et al [52] showed that in comparison with healthy individuals, patients with T1DM exhibited an increase in ROS generation, while plasma antioxidant status remained unaltered. Matteucci et al [53] demonstrated a disturbed antioxidant status in first-degree relatives of patients with T1DM, which may have been caused by a general pro-oxidative background resulting from an impaired erythrocyte redox system. In the present study, TaS in the siblings of patients with T1DM was significantly lower than in the controls, and the amount was comparable to that of patients with diabetes.…”
Section: Intra-erythrocyte Antioxidant Enzymes and Tasmentioning
confidence: 99%
“…In contrast, hydrogen peroxide suppresses NHE1 promoter activity and increases cell sensitivity to death triggers. These findings have important clinical implications on account of the observed erythrocyte NHE hyperactivity in relation to chronic states of oxidative stress in humans (Matteucci and Giampietro, 2000a; Matteucci and Giampietro, 2001; Matteucci and Giampietro, 2006; Matteucci and Giampietro, 2007a and b). Indeed, RBC NHE activity has been noted as being significantly higher in type 1 diabetes (T1D) family members, independently of the presence of renal disease.…”
Section: Erythrocyte Nhementioning
confidence: 73%
“…RBC vfcy has been further characterized in healthy subjects and T1D families with regard to: (a) the rate of electron transport in relation with body mass and metabolic efficiency, and (b) the modulating effects of diet and lifestyle on erythrocyte electron transfer system (Matteucci and Giampietro, 2006; Matteucci and Giampietro, 2007a). Among healthy controls, individuals with BMI ≤25 kg/m 2 had lower RBC vfcy in comparison with subjects who were overweight or obese.…”
Section: Potential Role Of Erythrocyte Pmors As Redox Biomarker In DImentioning
confidence: 99%
“…Such molecular information of cellular metabolism plays an important role in our understanding of the development and progression of cancer. Cancer can be influenced by many factors, such as diet, environment, and lifestyle [64]. Among all of the "omics" approaches, only metabolomics technology has provided a suitable tool in investigations of pathwayspecific metabolic alterations in the development and progression of cancer and could possibly be employed in the clinical diagnosis of cancer [59].…”
Section: An Overview Of Nmr-based Metabolomic Application In Cancer Rmentioning
confidence: 99%